Aeromedical evacuations in the Canadian North: does the presence of a physician alter rates? - Brendan Peddle; Philippe François Simon; Sean Waites; Cheri Bethune (International Journal of Circumpolar Health)
Patients in Nunavut rely exclusively on airplane to access medical care beyond the nursing stations in communities. This can take the form of scheduled flights for chronic and non-urgent issues or dedicated medevacs for emergencies. Each community is routinely visited by family physicians (FP) who provide in-person primary care. The frequency and duration of FP visits depends on the community size, with larger communities having longer and more frequent visits. During their visits, FPs can be called upon to assist in emergencies. This study provides a detailed portrait of the territory’s medical travels between 2012 and 2018. Contrary to our initial hypothesis, we show that the presence or absence of an FP in the community did not have a significant impact on the rates of medevacs. However, we found that the rates of non-urgent scheduled flights increased. Our findings provide in-depth information on the rates of medevacs and non-urgent travel in Nunavut. They also raise important questions for primary care in remote areas by demonstrating an increase in routine travel requirements when physicians are present in those communities. As health outcomes were not assessed, further studies are required before recommendations can be made to change the rate of FP visits.